Are Chinese university students more likely to exhibit a Surface approach to learning than other international students in Finland?. (August 2014) - Sakurai, Yusuke; Pyhältö, Kirsi; Lindblom-Ylänne, Sari
This article is based on a study which investigated whether Chinese international students at a university in Finland are more likely to rely on a Surface approach to learning and dismiss a Deep approach than are other international students in the same university educational context. In responding to a survey, students' scores with respect to the Deep approach and Organized Studying did not significantly differ between the groups. However, the Chinese students appeared slightly to exhibit the Surface approach to a greater extent, although this result was tentative when the students' extreme response styles were taken into account.